Mastering the learning curve of endoscopic mitral valve surgery - Aerts, Luca; Sardari Nia, Peyman (Frontiers in Cardiovascular Medicine, 2023)
Endoscopic mitral valve surgery is a challenging procedure. Surgical volume is mandatory to achieve sufficient proficiency and superior results. To this date the learning curve has proven to be challenging. Offering high-fidelity simulation based training for both residents as experienced surgeons can help in establishing and enlarging surgical competences in shorter time without intraoperative trial and error.